USING AI WHILE TEACHING ENGLISH FOR B1 LEVEL LEARNERS (KONFERENSIYA, 2025)
This article explores the integration of Artificial Intelligence (AI) tools in teaching English to B1 level learners. It examines how AI-based applications enhance vocabulary acquisition, improve speaking and listening skills, support grammar practice, and provide personalized learning pathways. The study highlights the pedagogical benefits of AI, discusses challenges in its implementation, and provides recommendations for effective classroom use. The findings show that AI significantly fosters autonomy, motivation, and language proficiency among intermediate students